Effect Of Ecommerce Post-Purchase Activities On Customer Retention In Shopee Indonesia - Margaretha Pink; Nicoline Djohan (Institute of Computer Science (IOCS), 2021)
The purpose of this paper is to understand the relationship between post-purchase activities with customer satisfaction and customer retention in Shopee Indonesia. This research is intended to provide deeper literature insight related to customer service, shipping, tracking, return, and order fulfilment in ecommerce setting which can be used as managerial guidance. Data from 412 respondents which are Shopee Indonesia users were collected through questionnaire using purposive sampling method and analyzed using SmartPLS version 3.0. Findings of the research shows significant positive effect of customer service, shipping, return and order fulfilment on customer satisfaction. It is also found that customer satisfaction leads to customer retention. This study aims to provide relevant knowledge regarding the importance of customer service, shipping, tracking, return, and order fulfilment in online shopping environment which can be implemented to satisfy and retain online customers.